Dying of success: Internet, place marketing and tourist apartments in Madrid - Martinez Martinez, Luz; Cuesta Cambra, Ubaldo; Roberts Martínez, Marion (Street Art & Urban Creativity, 2025)
The phenomenon of tourist apartments in Madrid is a reflection of the tensions between the globalized economy of tourism and the local needs for housing and social coexistence. Although tourism is a crucial economic engine for the city, its excessive growth through digital platforms has generated a series of problems such as gentrification, rising housing prices, insecurity and rejection. In this context, communication and place marketing tools are key elements to address this problem in a sustainable way. This article explores the communication flow about tourist apartments in Madrid and their perception of conflict in relation to the city council and the need for efficient communication strategies and place marketing.